Pemantauan Pembangkit Listrik Tenaga Mikrohidro (PLTMH) - Arif Gunawan; Arisco Oktafeni; Wahyu Khabzli (Jurnal Rekayasa Elektrika, 2013)
This research is motivated by electrical power shutting-down that frequently occurred in Riau province. Low electrical power supply as compared to the need causes lack of supply. Thus, new alternative electrical energy resource such as micro hydro is required. Micro hydro plant is an electrical power generators that uses water to rotate the turbine. This research designs a monitoring system for micro hydro plant. The monitored micro hydro plant employs water turbine that is constructed using bicycle pedal and a water pipe installed on the pedal . The pipe flows the water to energize the turbine. Turbine rotation will generate electricity. The amount of power resulted by generators depends on the number of turbine rotation. The power is used to turn on the lamp. Some sensors are used to monitor generator performance. Current, voltage, and rotation sensors are used to monitor the resulted current, voltage, the turbine rotation respectively. The output power is stored in the battery. The micro Arduino and the ethernet shield capture the monitored data and send it to the computers using Wi-Fi connection. Measurement results show that the output voltage produced by the generator is 10 Volts when the water volume is high. Finally, it is found that the micro hydro generator is able to supply 5 Watts to the load.